2017
DOI: 10.1186/s40479-017-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Standard 12 month dialectical behaviour therapy for adults with borderline personality disorder in a public community mental health setting

Abstract: BackgroundDialectical behaviour therapy (DBT) is noted to be an intervention with a growing body of evidence that demonstrates its efficacy in treating individuals diagnosed with borderline personality disorder (BPD). Evidence for the effectiveness of DBT in publicly funded community mental health settings is lacking however. No study to our knowledge has been published on the effectiveness of a 12 month standard DBT programme without adaptations for individuals with BPD in a publicly funded community mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
3
19
0
4
Order By: Relevance
“…Examples of such barriers include lack of support from public mental health authorities and programme leaders, and absence of organisational support (including staff turnover, and funding for administration, training and supervision). Given positive research outcomes on effectiveness of DBT in a separate study across four sites in the south of Ireland [ 40 ], a National Office for Suicide Prevention (established specifically to drive suicide and self-harm prevention strategies in the public health service in Ireland) agreed to fund and support a project team to coordinate a multi-site implementation of DBT in community settings at a national level [ 41 ]. As a result, the National DBT Project, Ireland was established in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such barriers include lack of support from public mental health authorities and programme leaders, and absence of organisational support (including staff turnover, and funding for administration, training and supervision). Given positive research outcomes on effectiveness of DBT in a separate study across four sites in the south of Ireland [ 40 ], a National Office for Suicide Prevention (established specifically to drive suicide and self-harm prevention strategies in the public health service in Ireland) agreed to fund and support a project team to coordinate a multi-site implementation of DBT in community settings at a national level [ 41 ]. As a result, the National DBT Project, Ireland was established in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…It has the highest number of randomised controlled trials (RCTs) investigating its efficacy in treating this disorder [ 1 ]. Both the UK Department of Health [ 2 ] and the American Psychiatric Association [ 3 ] advocate it as one of the leading treatments for BPD, and recent research supports its application in community settings [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comtois and colleagues [23] were the first to evaluate the effectiveness of DBT in a community mental health setting. Their study and subsequent effectiveness evaluations [24][25][26][27] have reported positive outcomes for individuals with BPD who participate in community based DBT programmes. In line with this, best practice guidelines for the delivery of evidence-based interventions in mental health services also recommend DBT for the treatment of BPD in community settings [28][29].…”
mentioning
confidence: 99%